On weights satisfying parabolic Muckenhoupt conditions. (January 2016) - Kinnunen, Juha; Saari, Olli
Abstract: This note collects results related to parabolic Muckenhoupt A p weights for a doubly nonlinear parabolic partial differential equation. A general approach is proposed, which extends the theory beyond the quadratic growth case. In particular, the natural parabolic geometry for the equation and the unavoidable time lag are incorporated in the definitions and results. The limiting Muckenhoupt conditions of A ∞ type are also discussed and several open questions are posed.